Role of Vaginal Microbiota Dysbiosis in Gynecological Diseases and the Potential Interventions - Han, Yiwen; Liu, Zhaoxia; Chen, Tingtao (Frontiers in Microbiology, 2021)
Vaginal microbiota dysbiosis, characterized by the loss of Lactobacillus dominance and increase of microbial diversity, is closely related to gynecological diseases, thus intervention on microbiota composition is significant and promising in the treatment of gynecological diseases. Currently, antibiotics and/or probiotics are the mainstay of treatment, which show favorable therapeutic effects but also bring problems such as drug resistance and high recurrence. In this review, we discuss the role of vaginal microbiota dysbiosis in various gynecological infectious and non-infectious diseases, as well as the current and potential interventions.